2008
DOI: 10.1037/a0014232
|View full text |Cite
|
Sign up to set email alerts
|

Good intentions gone awry: Assessing parental "miscarried helping" in diabetes.

Abstract: Miscarried helping" is a pattern of frustration and conflict surrounding diabetes management as caregivers escalate their efforts to ensure adequate self-care by their children. This paper describes the development of a new measure of this construct and preliminary assessment of its psychometric properties. The 15-item Helping for Health Inventory (HHI) was developed based on the theoretical concept of "miscarried helping." Parents of adolescents with poorly controlled diabetes (n ϭ 40) who were enrolled in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 29 publications
3
37
2
Order By: Relevance
“…25 Conversely, conflictual family relationships can disrupt children's treatment adherence. 41 One such pattern of conflict, defined as miscarried helping, is characterized by parents' well-intentioned attempts to help their children manage their chronic illness treatment that are perceived by children as intrusive. Over time, such interactional patterns can cause increasing tension and conflict in parent-child relationships that interfere with adaptive family communication and problem solving and eventually disrupt treatment adherence.…”
Section: Refining the Model Of Influences On Adherence To Pediatric Amentioning
confidence: 99%
“…25 Conversely, conflictual family relationships can disrupt children's treatment adherence. 41 One such pattern of conflict, defined as miscarried helping, is characterized by parents' well-intentioned attempts to help their children manage their chronic illness treatment that are perceived by children as intrusive. Over time, such interactional patterns can cause increasing tension and conflict in parent-child relationships that interfere with adaptive family communication and problem solving and eventually disrupt treatment adherence.…”
Section: Refining the Model Of Influences On Adherence To Pediatric Amentioning
confidence: 99%
“…All scores are converted to T-scores; higher scores reflect a more intense mood rating for the respective emotional domain. Internal consistency, test-retest reliability and validity are excellent (McNair et al, 1992 (Harris et al, 2008). For this study, an adapted version of the HHI published for children with chronic pain was used (Fales, et al, 2014).…”
Section: Parent Problem Solving Skills-parents Completed the Social Pmentioning
confidence: 99%
“…Parents completed the Helping for Health Index (HHI), a 15-item questionnaire originally designed to assess miscarried helping among parents of youth with diabetes, and has demonstrated good reliability and validity in that population (Harris et al, 2008). For this study, an adapted version of the HHI published for children with chronic pain was used (Fales, et al, 2014).…”
Section: Parent Miscarried Helping-miscarried Helping Was Originally mentioning
confidence: 99%
“…The construct of ''miscarried helping,'' when this leads to conflict, has proven to be consistent across a diverse group of families of youth with poorly controlled diabetes. 8 Yet, research suggests that there is no specific ''family profile'' for predicting miscarried helping in families of youth with diabetes. 9 Various studies have demonstrated that diabetes-specific and general family conflicts are both associated with lower treatment adherence in adolescents.…”
Section: Introductionmentioning
confidence: 99%